Unprecedented large-scale aquifer recovery through human intervention - Di Long; Yuancheng Xu; Yingjie Cui; Yanhong Cui; James J. Butler; Liang Dong; Longfeng Wang; Dongyong Liu; Yoshihide Wada; Litang Hu; Guoying Bai; Binghua Li; et al. (Nature Communications)
Abstract Groundwater depletion is a critical global challenge, particularly in intensively cultivated drylands, with few documented cases of successful recovery. Here, we report a striking reversal of long-term groundwater decline in the North China Plain, one of the world’s most severely depleted aquifers. Based on a comprehensive analysis of groundwater levels from over 2000 monitoring wells spanning the past two decades, we show that groundwater levels have risen at an average rate of ~0.7 m year− 1 since 2020, surpassing 2005 levels by 2024. This recovery is driven by a combination of large-scale surface water diversion from the humid south and stringent groundwater pumping regulations, further amplified by wet years (e.g., 2021). From 2005 to 2023, these policies reduced annual groundwater abstraction by ~12 km3 and increased environmental water allocations to over 7 km3 since 2021, promoting aquifer recharge and restoring environmental flows. Our findings demonstrate that rapid, large-scale groundwater recovery is achievable through integrated water management and targeted policy interventions across extensive regions (~130,000 km2).